Meningkatkan Daya Saing UMKM Perikanan Melalui E-commerce - Alpiani, Alpiani; Amri, Andi; Tahang, Hamzah; Fakhriyyah, Sitti; Wahid, Abd (LPPM Universitas HKBP Nommensen, 2025)
The development of digital technology has opened up opportunities for MSMEs to expand their product marketing through the use of e-commerce. However, many MSMEs in the fishery sector in Takalar Regency have not yet optimally utilized digital platforms. This condition encourages the need for efforts to increase digital literacy and the capacity of fishery MSMEs in online marketing. The Fisheries Agribusiness Study Program at Hasanuddin University (Unhas) conducted community service activities with the theme